SWOT Analysis as The Basis of The Marketing Mix in Increasing Income in PT. Elteha International Singaraja - Kusuma, Gusti Putu Eka; Nurkariani, Ni Luh (International Journal of Social Science and Business, 2022)
The development of business in Indonesia is getting sharper with complexity, competition, change, and uncertainty. In running a business, of course there is a problem that interferes with the running of the business, both internally and externally. This situation creates sharp competition between companies including shipping companies, thus forcing companies to pay more attention to the internal and external environment that can affect the company, so that companies know what marketing strategies are and how they should be applied within the company. The purpose of this study is to find out the SWOT analysis at PT. Elteha International Singaraja branch and to know the SWOT analysis as the basis for the marketing mix. The analytical techniques used in this study are Data Reduction, Data Display / Data Presentation and Drawing Conclusions and Verification. The results showed that PT. Elteha International Singaraja is a business engaged in the field of expeditions. Determination of marketing strategy using SWOT analysis method. Data from internal and external were obtained from the results of unstructured interviews with the resource persons, namely the head of representatives of PT. Elteha International Singaraja, employee at PT Kerta Gaya Pusaka, relation to PT. Elteha International Singaraja and consumers remain at PT. Elteha International Singaraja concludes as follows, Internal and external factors that are a strength in increasing revenue at PT. Elteha International Singarajabranch are speed in delivery compared to other services, the company also has offices spread throughout Indonesia, always providing security for the goods to be sent , a factor that becomes a weakness in increasing revenue at PT. Elteha International Singaraja branch.